Sequential contralateral facial nerve palsies following COVID-19 vaccination first and second doses. Issue 7 (19th July 2021) - Burrows, Abigail; Bartholomew, Theo; Rudd, James; Walker, David
Abstract : A 61-year-old man presented to the ENT emergency clinic with a history of unilateral facial nerve palsy occurring shortly after each dose of the Pfizer-BioNTech COVID-19 vaccine. The first episode developed 5 hours after administration of the first dose and the second 2 days after administration of the second dose. Investigations at initial presentation to the emergency department were unremarkable, and the patient was diagnosed with Bell's palsy on both occasions. We describe the first case of Bell's palsy occurring after each dose of any UK-approved COVID-19 vaccine. Single episodes of unilateral facial nerve palsies have been reported in clinical trials and in subsequent case reports. There has been no evidence, however, of an episode after each dose. We also describe the earliest onset of symptoms from timing of administration of the vaccine, further suggesting the Bell's palsy was associated with the vaccine.